Inactivation of Streptococcus pyogenes extracellular cysteine protease significantly decreases mouse lethality of serotype M3 and M49 strains. - Lukomski, S (1997)
Cysteine proteases have been implicated as important virulence factors in a wide range of prokaryotic and eukaryotic pathogens, but little direct evidence has been presented to support this notion. Virtually all strains of the human bacterial pathogen Streptococcus pyogenes express a highly conserved extracellular cysteine protease known as streptococcal pyrogenic exotoxin B (SpeB). Two sets of isogenic strains deficient in SpeB cysteine protease activity were constructed by integrational mutagenesis using nonreplicating recombinant plasmids containing a truncated segment of the speB gene. Immunoblot analyses and enzyme assays confirmed that the mutant derivatives were deficient in expression of enzymatically active SpeB cysteine protease. To test the hypothesis that the cysteine protease participates in host mortality, we assessed the ability of serotype M3 and M49 wild-type strains and isogenic protease-negative mutants to cause death in outbred mice after intraperitoneal inoculation. Compared to wild-type parental organisms, the serotype M3 speB mutant lost virtually all ability to cause mouse death (P < 0.00001), and similarly, the virulence of the M49 mutant was detrimentally altered (P < 0.005). The data unambiguously demonstrate that the streptococcal enzyme is a virulence factor, and thereby provide additional evidence that microbial cysteine proteases are critical in host-pathogen interactions.